A budget impact analysis of lenalidomide in multiple myeloma Egyptian patients. (2nd October 2020) - Elsisi, Gihan Hamdy; Carapinha, João L.; Afify, Rania; Elmoty, Mohamed Abd; Khalaf, Mohamed
Abstract: Introduction: The aim of this study was to estimate the budget impact of lenalidomide and dexamethasone (RD) versus bortezomib, cyclophosphamide and dexamethasone (VCD) in newly diagnosed multiple myeloma (NDMM) and relapsed refractory (RR) MM patients, from the perspective of the Egyptian Ministry of health (MoH). Methods: Two budget impact dynamic models were conducted to assess the budget impact of RD entry over a 3-year period. The clinical data for the modeled cohorts were based on published articles. Total annual medical costs associated with non-progression and progression disease states included the sum of estimated costs for adverse effects management, concomitant treatments, hospitalization and the follow up were measured. Deterministic sensitivity analyses were performed. Results: The target population in a given year was estimated to include 245 patients with RRMM and 291 patients with NDMM receiving RD versus VCD. In RRMM, the annual budget savings of lenalidomide entry were estimated at EGP −1, 103, 969, −3, 362, 793 and −5, 949, 228 at year 1, year 2 and year 3, respectively. In NDMM, the annual budget savings of lenalidomide entry were estimated at EGP869, 415, −1, 779, 776 and −2, 139, 311 at year 1, year 2 and year 3, respectively, to the payer after lenalidomide entry. The model results in RRMM were most sensitive to variations in patients eligible to transplantation in RRMM. In NDMM, the model results were most sensitive to the market share of VCD in the first year. Conclusion: The results of our BI models suggest that not only does RD treatment have an effect on the budget, but also has major cost savings in other areas which are very important while considering the total costs of MM treatment. This study results provided evidence-based information to the MoH that will help in decision making of whether to implement RD as a treatment intervention or not.